Mengubah Sampah Menjadi Rezeki: Analisis Actors Dalam Pemberdayaan Masyarakat Pada Pengelolaan Sampah. - Sahrul; Setia Budhi (Huma: Jurnal Sosiologi, 2023)
In the ACTORS theory, there is an ACTORS framework consisting of Authority, Confidence and Competence, Trust, Opportunities, Responsibilities, and Support. This study aims to determine and describe the ACTORS and impacts in community empowerment through waste management at the Baiman Main Waste Bank, Alalak Utara Village, Banjarmasin City. This research uses qualitative research. The data collection techniques used in this research are observation, interviews and documentation. The results of research through the ACTORS framework show that the manager's authority in making decisions related to programs and activities in the waste bank is an authority that cannot be intervened by the Banjarmasin city government. Through trust that is well established between managers and customers, it provides opportunities for customers to participate in training and making recycled products. By participating in training and making recycled products, customers gain economic capacity. The opportunities provided by the Waste Bank through training in making recycled products foster an entrepreneurial spirit in the community. Support from the Banjarmasin City Government in providing transportation facilities to support waste transportation activities. Based on the ACTORS analysis, there are no points of belief and responsibility in the empowerment activities and programs of the Banjarmasin City Baiman Main Waste Bank. The programs carried out by Baiman Main Waste Bank have an impact on the community including: the health and environmental impact of sorting activities, the impact of sorting activities on gender equality, economic impacts and business opportunities, impacts related to the 3R principle, through the reuse of waste.